Egg Allergy in infancy - R Shrestha; D Shrestha; R Poudyal; N Mishra (Nepal Journal of Dermatology, Venereology & Leprology)
Egg allergies are one of the most common allergies of childhood and the reactions may vary from mild to severe. A family history of egg allergy or atopy is a risk factor for egg allergy. Most food-induced allergic reactions occur on first known oral exposure, especially in the case of eggs and peanuts. We report a case of nine months old infant who developed egg allery (contact dermatitis) after contact with egg white, with a positive family history of atopy and egg allergy.